Annotated bird sighting list for winter 1980 and 1981 compiled by Francis L. Moore - Moore, Francis L.et al (1981)
An annotated list of birds sighted by Francis L. Moore and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed